2024
DOI: 10.7759/cureus.55484
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Radiation Hazards and Knowledge About Radiation Protection Among Medical Students at the Northern Border University, Arar

Pakeeza Shafiq,
Yasir Mehmood

Abstract: Studies have shown that medical students and doctors are not well equipped with knowledge of radiation hazards and their protection. This lack of knowledge may cause harm to patients and healthcare professionals. Objectives To compare the awareness of radiation hazards and knowledge about radiation protection among medical students at Northern Border University, Arar, Saudi Arabia, with and without prior teaching. Methods and materials This cross-sectional study was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In order for healthcare personnel to be competent in radiation protection, they must first know radiation and the relationship between radiation and the devices used (Paolicchi et al 2016). Previous studies have also shown that the adequacy of the theoretical knowledge of the staff triggers their self-confidence in practical applications (Saracli & Ulucan 2021, Shafiq & Mehmood 2024.…”
Section: Introductionmentioning
confidence: 99%
“…In order for healthcare personnel to be competent in radiation protection, they must first know radiation and the relationship between radiation and the devices used (Paolicchi et al 2016). Previous studies have also shown that the adequacy of the theoretical knowledge of the staff triggers their self-confidence in practical applications (Saracli & Ulucan 2021, Shafiq & Mehmood 2024.…”
Section: Introductionmentioning
confidence: 99%